Evaluation of the Success of Breastfeeding Support Groups on Exclusive Breastfeeding Coverage in the Central Sulawesi Province - Gusman Arsyad; Mercy Joice Kaparang; Nurdin Rahman; Sri Nurbaeti; Vivi Putri Damayanti; Sunarto Sunarto (Humanistic Network for Science and Technology (HNST), 2022)
Mother's readiness to exclusively breastfeed her baby is influenced by family factors, health workers, and peer support. The purpose of the study was to evaluate the success of the exclusive breastfeeding support group (KP-ASI) on the coverage of exclusive breastfeeding in the province of Central Sulawesi. This type of research was experimental with posttest only control group design. The research locations were three regencies, namely Banggai Regency, Donggala Regency and Poso Regency. The research period was two months (August-September 2021). Sample size was 114 respondents, divided into two groups, namely 57 respondents from the intervention group and 57 respondents from the control group. The intervention group was given exclusive KP-ASI support treatment, while the control group was given no treatment. Data analysis using Mann Whitney test. The results of the Kruskal Willas test obtained p-value of 0.000. The statistical meaning stated that there was a difference in support between the health cadre group, the grandma group and the youth group for exclusive breastfeeding coverage. The conclusion of the study was that the health cadre group as supporters of exclusive breastfeeding was more effective in increasing the coverage of exclusive breastfeeding than the grandma group and the youth group. Keywords: breast milk care group; exclusive breastfeeding; health cadre group; grandma group; youth group